2005
DOI: 10.1007/s11104-004-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of relationships between physiological parameters and growth performance of rice (Oryza sativa L.) seedlings under salinity stress using multivariate analysis

Abstract: Knowledge of relationships between physiological parameters and growth performance of seedlings and respective genotypic differences would permit selection of salt tolerance at early growth stages. The goals of this study were to investigate the relationships between physiological parameters and growth performance and quantify the respective genotypic differences using multivariate analysis.. Plants of thirty-one genotypes were grown in sand tanks in a greenhouse and irrigated with Yoshida nutrient solution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 27 publications
(30 reference statements)
1
45
0
1
Order By: Relevance
“…Since the interspecifi c group is the product of the crosses between the O. sativa and O. glaberrima species (Jones et al, 1997), some of the genotypes in this group may have acquired mechanisms for salt tolerance from the O. sativa parent. There exist genotypic differences in salt tolerance among O. sativa genotypes (Zeng, 2005). Our result suggested that some salt-tolerant interspecific progeny produced from the crosses between CG14 and WAB56-104 have acquired its salt tolerance from the O. sativa parent.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Since the interspecifi c group is the product of the crosses between the O. sativa and O. glaberrima species (Jones et al, 1997), some of the genotypes in this group may have acquired mechanisms for salt tolerance from the O. sativa parent. There exist genotypic differences in salt tolerance among O. sativa genotypes (Zeng, 2005). Our result suggested that some salt-tolerant interspecific progeny produced from the crosses between CG14 and WAB56-104 have acquired its salt tolerance from the O. sativa parent.…”
Section: Discussionmentioning
confidence: 63%
“…However, there exist genotypic differences among rice genotypes in the response to salinity (Zeng, 2005). Seedling and fl owering stages are most sensitive to salinity stress (Lutts et al, 1996;Gregorio et al, 1997).…”
mentioning
confidence: 99%
“…Using conventional approaches, genotypes are scored on single characters and the ranking is often inaccurate and cumbersome (Zeng et al, 2002;Zeng, 2005;Lee at al., 2005). Cluster analysis constitutes a multivariate statistical method that can be effectively used to characterize, classify and rank numerous plant cultivars (Jolliffe et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Cluster analysis constitutes a multivariate statistical method that can be effectively used to characterize, classify and rank numerous plant cultivars (Jolliffe et al, 1989). Such technique has been used successfully to screen wheat, rice and potato genotypes under drought or salinity stress conditions which were further grouped into homogeneous groups based on their growth performance (Yasir et al, 2013;El-Hendawy et al, 2011, 2005Zeng et al, 2002;Zeng, 2005;Khrais et al, 1998). It is also interesting to explore the relationships among the growth traits in order to define those that are highly correlated with high yield so that they can be further incorporated in a breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore efficient and accurate indices and criteria for identifying salt-tolerance in Brassicas and related species are needed. The multivariate cluster analysis method was recommended as the best criteria for the identification of salt tolerance in crop species such as rice [18,28,29], green gram [30], wheat [19], tomato [31], sugarcane [32], peanut [33], cauliflower [34]. As pointed out by Khrais et al [35] and Zeng et al [18], the advantages of using a multivariate analysis in the evaluation of salt tolerance are hat it allows: 1) a simultaneous analysis of multiple t Table 3. parameters to increase the accuracy of the genotype ranking; 2) the ranking of genotypes even when plants are evaluated at different salt levels and salt tolerance varies with salinity levels, especially when the salt tolerance indices are averaged across salt levels; and 3) a more convenient and accurate estimation of salt tolerance among genotypes by simply adding the numbers in cluster group ranking at different salt levels.…”
Section: Discussionmentioning
confidence: 99%